The Red Room - Pearson, Ridley (Pearson, Ridley. Risk agent novel, 2014)
"In the newest international thrill ride from New York Times-bestselling author Ridley Pearson, John Knox and Grace Chu, the incomparable and often incompatible duo, team up again, this time in the exotic 'city between two worlds,' Istanbul. What's it like to see yourself in a picture you never knew was taken? John Knox is an expert at surveillance and delicate, international dealings. So he is understandably thrown when David 'Sarge' Dulwich, his contact at Rutherford Risk, hands him a photo of a transaction he recently facilitated in the Middle East. More curious to him, he's shown that photo while in the Red Room, the private security company's highly secure underground bunker, where eavesdropping is impossible and privacy ensured. Why all the cloak-and-dagger? Knox is pressured into accepting a job as an art broker in the mysterious Istanbul, a city situated on two continents where East meets West and Islam meets Christianity. It is a melting pot of spies, terrorists, and conflicting interests. Teamed with smart, quick, and fearless Grace Chu, Knox must navigate a murky operation, the only goal of which is to spend five minutes in the proximity of a man they've never met. Why? What can it possibly matter? And why are so many others bound and determined to see it never happens--at any cost? "--